Workload, roles and staff development in relation to managing library and media in Terengganu - Muhamad Nur Kamal, Awang (2016)
In order to improve the education system, the Government always puts out extra efforts, especially at the school level. These efforts have brought the establishment of school libraries and the post of library and media teacher (LMT) at all schools in Malaysia. Other than the LMT post, the teachers have to teach subjects according to their options and cater to other tasks assigned by the school. The main objective of this study is to investigate the workload of LMT duties and whether or not they comply the guided role. Furthermore, students' perceptions towards the LMT roles have also been studied. This research also reviewed the suitability of training whether they fulfill the needs of the teachers. The researcher has carried out a two phase study in the state of Terengganu, Malaysia. In the first phase, a survey was distributed to 268 LMTs and 194 students. An interview and document analysis was then conducted to complement the questionnaires and provide wider views to answer the research questions.The data were analysed for trangulations and to answer the research questions. The outcome of the data analysis was that the LMTs are facing excessive workload and conflicts to comply the guided role, since they are burdened with many other posts as well. This research found that LMTs only complied with 10 out of 18 of the guided role. Many of them are commited to fulfiling the role of LMTs, but they still need training and development in the library and information science, in addition to their task conflicts as mentioned previously. Almost 90% of students show appreciation for the post of LMT, consider it important in their learning and value their positive influence on the students' academic success. They believe that an efficient LMT is always friendly, helpful and disciplined. The training of LMTs are appropriate, however they still need advanced courses to become efficient LMTs. It is hoped that the LMTs and the government can also utilise the information from the study to recognise the conflicts faced by the LMTs and take several crucial measures to overcome the problem overburdening the LMTs with tasks.